Hubungan asupan serat dengan angka kejadian kanker kolorektal di RSUP Sanglah Denpasar tahun 2016 - 2017 - Rani Pradnya Swari; Made Agus Dwianthara Sueta; Made Suka Adnyana (DiscoverSys Inc., 2019)
Background: Colorectal cancer is one of the most common cancer in Indonesia. The etiology of colorectal cancer is still unknown, but many risk factors believed may causing colorectal cancer, one of them is fiber intake of foods consumed every day like vegetables, fruits, and peanuts. There is an instrument that can be used to assess fiber intake per day.Aim: The study aimed to know how the correlation between fiber intake and colorectal cancer patient are in Sanglah General Hospital.Method: The design is a case-control analytic study, obtained total of 104 samples that divided into case group (52 samples) and control group (52 samples), in which secondary data with medical record data and also primary data with questionnaire are collected. Data were analyzed using the SPSS program.Result: Of the 104 samples that divided into case group and control group with 1:1 ratio, patients who diagnosed with colorectal cancer had a history of low fiber intake higher 6.75 times than peoples who not diagnosed with colorectal cancer (OR=6.75; 95% CI 2.85-15.96; P<0.001).Conclusion: Patients who diagnosed with colorectal cancer had a history of low fiber intake per day higher 6.75 times than samples which did not diagnose with colorectal cancer.